Outcomes of Hip Arthroscopy in Patients with Tönnis Grade-2 Osteoarthritis at a Mean 2-Year Follow-up: Evaluation Using a Matched-Pair Analysis with Tönnis Grade-0 and Grade-1 Cohorts. (15th June 2016) - Chandrasekaran, Sivashankar; Darwish, Nader; Gui, Chengcheng; Lodhia, Parth; Suarez-Ahedo, Carlos; Domb, Benjamin G.
Abstract : Background: Osteoarthritis adversely impacts hip arthroscopy outcomes. The purpose of this study was to conduct a matched-pair analysis with a mean follow-up of 2 years to evaluate the outcomes following hip arthroscopy in patients with Tönnis grade-2 osteoarthritis. Methods: Data were prospectively collected on all patients undergoing hip arthroscopy during the study period from April 2008 to December 2012. Patients were excluded if they had previous hip conditions. Patients were categorized into Tönnis grade-0, grade-1, or grade-2 osteoarthritis groups and were matched in a 1:1 ratio according to age within 5 years, sex, and body mass index. Four patient-reported outcome scores, a visual analog scale (VAS) score for pain, patient satisfaction level, and rates of revision hip arthroscopy and conversion to total hip arthroplasty were recorded. Results: During the study period, 1, 412 hip arthroscopies were performed. Of those, 1, 079 satisfied the inclusion criteria, and 935 (86.7%) of them had a follow-up of 2 years. Seven hundred and thirty-eight, 154, and 43 patients had Tönnis grade-0, grade-1, and grade-2 osteoarthritis, respectively. Thirty-seven patients were matched in each group. All groups demonstrated a significant improvement in patient-reported outcomes and VAS scores. A good-to-excellent result was seen in 69.7%, 75.8%, and 65.4% of the patients in the Tönnis grade-0, grade-1, and grade-2 groups, respectively. No significant difference among the groups was found with respect to the mean change in patient-reported outcomes, VAS scores, and patient satisfaction level. There was no significant difference in the rate of revision arthroscopy. Tönnis grade-2 hips had an odds ratio for conversion to total hip arthroplasty of 7.73 (95% confidence interval [CI], 2.00 to 29.83) compared with Tönnis grade-0 hips and 4.36 (95% CI, 1.38 to 13.4) compared with Tönnis grade-1 hips. Conclusions: Hips with Tönnis grade-2 osteoarthritis had a significantly higher rate of conversion to total hip arthroplasty at the 2-year follow-up compared with matched cohorts of Tönnis grade-0 and grade-1 hips. Thus, hip arthroscopy has a limited role as a joint preservation procedure in select patients with Tönnis grade-2 osteoarthritis. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.